Library Policy and Service Delivery in Federal Universities in South-South Nigeria - Onwuekwe , Chibueze Nobert (University of Dar es Salaam Library Journal, 2024)
This study investigated the relationship between library policy and service delivery in South-South Nigeria federal universities. Two research questions guided this study, with hypotheses tested at a 0.05 significance level. The study employed a correlational research design. The population consisted of 115 professional librarians. Since the sample size was equal to the population, the study adopted a census approach and a structured questionnaire with a 4-point Likert scale for data collection. Data analysis utilised the Pearson Product Moment Correlation (PPMC) via the Statistical Package for Social Sciences (SPSS). The results indicate a significant relationship between reference service policy, serials management policy, and service delivery in federal universities of South-South Nigeria. Based on the findings of this study, the following recommendations are made: Firstly, given the significant relationship between reference service policy and service delivery, libraries should prioritise the effective implementation of reference service policies to enhance service delivery. Secondly, considering the significant relationship between serials management policy and service delivery, library management should prioritise acquiring new journals in line with the serials management policy to meet users’ information demands, thereby enhancing library service delivery. Keywords: Library reference service policy, serial management policy, service delivery federal universities, South-South Nigeria https://dx.doi.org/10.4314/udslj.v19i2.7